Determination and Stability of Gonadal Sex - Schlessinger, David; Garcia-Ortiz, Jose-Elias; Forabosco, Antonino; Uda, Manuela; Crisponi, Laura; Pelosi, Emanuele (Journal of andrology, 2010)
The discovery that the SRY gene induces male sex in humans and other mammals led to speculation about a possible equivalent for female sex. But females are proving to be more complicated. Several master genes appear to be autonomously involved, and female sex determination seems to remain relatively labile. Partial loss of function of the transcription factor FOXL2 leads to premature ovarian failure in women; and in animal models, Foxl2 is required for folliculogenesis as well as for maintenance, and possibly induction, of female sex determination. In the germ line, oocytes apparently form normally even in the absence of Foxl2, dependent on genes that include female‐specific factors such as Fig‐alpha, Nobox, etc. In the soma, ablation of Foxl2 or the independently expressed gene Wnt4 (likely downstream of Rspo1) can produce partial testis differentiation in XX mice, and the double knockout results in the formation of tubules and spermatogonia. This indicates that at least 2 autonomous ovarian pathways are required to antagonize testis differentiation in females, a finding that is being increasingly corroborated by studies in goats and nonmammalian vertebrates. In recent expression profiling of mouse ovaries that lack Foxl2 alone or in combination with Wnt4 or Kit/c‐Kit, we found that following Foxl2 loss, early testis genes (including the downstream effector of Sry, Sox9) and several novel ovarian genes were consistently dysregulated during embryo‐fetal development. The results support the proposal of dose‐dependent Foxl2 function and antitestis action. A partial working model for somatic development and sex determination is presented in which Sox9 is a direct antagonist of Foxl2 in the supporting cell lineage.